Type 2 Diabetes Mellitus in Patients with Different Types of Thyroid Nodular Lesions Among Western Romanian Patients: A Comprehensive Clinical, Biochemical, and Hormonal Analysis - Mervat Matei; Sergiu-Ciprian Matei; Flavia-Medana Petrașcu; Ioana Golu; Melania Balaş; Daniela Amzăr; Ana-Maria Ungureanu; Bianca Roxana Natarâş; Mihaela Maria Vlad (Medicina)
Background and Objectives: The prevalence of thyroid nodules and type 2 diabetes mellitus (T2D) has increased. This study firstly aims to assess the prevalence of T2DM among thyroid nodules patients who underwent total thyroidectomy in the Western Romanian population. By focusing on the biochemical and hormonal parameters, it also aims to provide insights into possible connections between T2D and different types (benignant or malignant) of thyroid nodules. Materials and Methods: A total of 926 patients who underwent total thyroidectomy were analysed, comprising 99 (10.7%) T2D patients and 827 (89.3%) non-diabetic patients (non-T2D). Results: This study’s results revealed an increased prevalence of T2D among thyroid nodules patients. Among these patients, higher values of FT4 and inflammatory markers and a higher prevalence of malignant nodules (55%, p = 0.001) were noted. Conclusions: Our study revealed an increased prevalence of T2D among thyroid nodules patients. The biochemical profile of thyroid nodules in T2D patients presents aspects, like elevated FT4 and inflammatory markers, which should be considered in their clinical management. Furthermore, a T2D patient seems to be more likely to develop thyroid malignancies. Thyroid screening strategies in diabetic patients should be considered.